Climate Change and Grapevines: A Simulation Study for the Mediterranean Basin*. (16th December 2014) - Ferrise, Roberto; Trombi, Giacomo; Moriondo, Marco; Bindi, Marco
Abstract: The present paper aims to assess the impacts of climate change on grapevine cultivation in the Mediterranean basin by using three regional climatic models (RCMs), which were designed specifically for high-resolution simulation of climate in that region. RCM outputs were used to feed a grapevine growth simulation model, which was developed, tested, and calibrated for the Sangiovese variety. The study area was identified by implementing a bioclimatic classification of the regions based on the Winkler Index (ranging from 1, 700 to 1, 900 thermal units). The results indicated that the projected increasing temperatures will result in a general acceleration and shortening of the phenological stages compared to the present period. Accordingly, the reduction in time for biomass accumulation negatively affected the final yield. Few exceptions were found in the northern and central regions of the study area (southern France and western Balkans) for which changes in climatic conditions were not limiting and the crop benefited from the enhanced atmospheric concentration of carbon dioxide. (JEL Classifications: Q100, Q540)